2020
DOI: 10.1177/2167696820922052
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Examining Dual Enrollment as a Strategy for Easing the Transition to College and Career for Emerging Adults

Abstract: Successfully transitioning to adulthood requires a successful transition from high school into college or the workforce. Yet for many emerging adults, this transition is not successful, leading to disengagement from school and work. Dual enrollment, where high school students enroll in college coursework, may help to facilitate this important life transition. This study applied propensity score matching to statewide administrative data to investigate the effects of dual enrollment on college and early labor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Our findings largely indicating a null relationship between DE coursetaking and students' likelihood of borrowing capture important nuances by examining the long-term financial implications of DE participation. Despite prior work showing the positive influence of DE participation on earnings (Henneberger et al, 2020;Phelps & Chan, 2017), DE course-taking does not appear to be an effective approach for students seeking to attend college without incurring student loan debt. One explanation for the null findings in the aggregate and across multiple subgroups is that the DE credits earned may not be transferable toward students' postsecondary degree plan.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Our findings largely indicating a null relationship between DE coursetaking and students' likelihood of borrowing capture important nuances by examining the long-term financial implications of DE participation. Despite prior work showing the positive influence of DE participation on earnings (Henneberger et al, 2020;Phelps & Chan, 2017), DE course-taking does not appear to be an effective approach for students seeking to attend college without incurring student loan debt. One explanation for the null findings in the aggregate and across multiple subgroups is that the DE credits earned may not be transferable toward students' postsecondary degree plan.…”
Section: Discussionmentioning
confidence: 80%
“…An (2013a) used nationally representative datasets and found that dually enrolled students with low socioeconomic status (SES) were more likely to obtain a college degree than their more affluent peers, but this disparate effect was not found for students' first-year GPA based on their SES (An, 2013b). This finding was consistent with DE's stronger effects on college enrollment, persistence, and completion for students of color and low-income students (Henneberger et al, 2020;Karp et al, 2007). On the contrary, Taylor (2015) noted that while DE is positively associated with college enrollment and degree completion, its effect sizes were smaller for low-income students and students of color.…”
Section: Dual Enrollment and Student Outcomesmentioning
confidence: 92%
See 2 more Smart Citations
“…The academic benefits associated with taking DE courses appear to be stratified on students' sociodemographic characteristics. While some studies found that economically and racially minoritized students may benefit more from DE's positive effects in terms of postsecondary access, persistence, and degree attainment (An, 2013a;Henneberger et al, 2020;Karp et al, 2007), this disparate effect was not found for their first-year GPA (An, 2013b). On the contrary, Taylor (2015) used Illinois' administrative data and found smaller effect sizes for economically and racially minoritized students when examining the relationship between DE participation and college success.…”
Section: The Role Of De Programs In Postsecondary Access and Equitymentioning
confidence: 99%